翻訳可能分子およびその合成 (2025)
A range of therapeutic mRNA molecules expressible to provide a target polypeptide or protein. The RNA molecules can contain one or more 5-methoxyuridines and 5-methylcytidines. Further provided are DNA templates, which can be transcribed to provide a target mRNA, and can have altered nucleotides, such as reduced deoxyadenosines. Also provided are processes for making the therapeutic mRNA molecules. The RNA molecules can be translated in vitro or in vivo to provide an active polypeptide or protein. The RNA molecules can be included in a composition used for preventing, treating, or ameliorating at least one symptom of a disease or condition in a subject in need thereof.